Utilização de microemulsões como agentes modificadores de superfícies para remoção de íons metálicos - Moura, Maria Carlenise Paiva de Alencar (2001)
The heavy metals are used in many industrial processes and when discharged to the environment can cause harmful effects to human, plants and animals. The adsorption technology has been used as an effective methodology to remove metallic ions. The search for new adsorbents motivated the development of this research, accomplished with the purpose of removing Cr (III) from aqueous solutions. Diatomite, chitosan, Filtrol 24TM and active carbon were used as adsorbents. To modify the adsorbent surface was used a bicontinuous microemulsion composed by water (25%), kerosene (25%), saponified coconut oil (10%) and as co-surfactant isoamyl or butyl alcohols (40%). With the objective of developing the best operational conditions the research started with the surfactant synthesis and after that the pseudo-ternary diagrams were plotted. It was decided to use the system composed with isoamyl alcohol as co-surfactant due its smallest solubility in water. The methodology to impregnate the microemulsion on the adsorbents was developed and to prepare each sample was used 10 g of adsorbent and 20 mL of microemulsion. The effect of drying time and temperature was evaluated and the best results were obtained with T = 65 ºC and t = 48 h. After evaluating the efficiency of the tested adsorbents it was decided to use chitosan and diatomite. The influence of the agitation speed, granule size, heavy metal synthetic solution concentration, pH, contact time between adsorbent and metal solution, presence or not of NaCl and others metallic ions in the solution (copper and nickel) were evaluated. The adsorption isotherms were obtained and Freundlich and Langmuir models were tested. The last one correlated better the data. With the purpose to evaluate if using a surfactant solution would supply similar results, the adsorbent surface was modified with this solution. It was verified that the adsorbent impregnated with a microemulsion was more effective than the one with a surfactant solution, showing that the organic phase (kerosene) was important in the heavy metal removal process. It was studied the desorption process and verified that the concentrated minerals acids removed the chromium from the adsorbent surface better than others tested solutions. The treatment showed to be effective, being obtained an increase of approximately 10% in the chitosan s adsorption capacity (132 mg of Cr3+ / g adsorbent), that was already quite efficient, and for diatomite, that was not capable to remove the metal without the microemulsion treatment, it was obtained a capacity of 10 mg of Cr3+ / g adsorbent, checking the applied treatment effectiveness